2019
DOI: 10.20944/preprints201908.0185.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Hypo-Hydration on Mood and Cognition is Influenced by Electrolyte in a Drink and Its Colour: A Randomised Trial

Abstract: Traditionally it has been thought necessary to lose 2% of body mass due to dehydration, before functioning is disrupted, although recently adverse effects have been reported with a loss of 0.5-0.7%. It is, however, unclear whether the response to small decreases in mass reflects dehydration, mechanisms that help to adapt to a loss of bodily fluid, or a placebo effect. Individuals were therefore subject to a temperature of 30°C for three hours, and mood and cognition monitored. To explore the possibilit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Considerable variance in outcomes was also observed in studies including a rehydration or euhydration component ( Figure 5). Of the 27 rehydration studies, 16 studies identified improvements to EF-related tasks as a function of rehydration or euhydration, primarily to working memory or shortterm memory 22,38,42,45,47,[49][50][51]57,59 and attention/inhibitory control. 30,31,32,35,39,42,59 Of the remaining studies, several found dose-dependent effects or effects that required the inclusion of 1 or more covariates or analysis of interaction effects; however, these results are not included as positive findings here.…”
Section: Effect Of Rehydration or Hydration Status On Efmentioning
confidence: 99%
“…Considerable variance in outcomes was also observed in studies including a rehydration or euhydration component ( Figure 5). Of the 27 rehydration studies, 16 studies identified improvements to EF-related tasks as a function of rehydration or euhydration, primarily to working memory or shortterm memory 22,38,42,45,47,[49][50][51]57,59 and attention/inhibitory control. 30,31,32,35,39,42,59 Of the remaining studies, several found dose-dependent effects or effects that required the inclusion of 1 or more covariates or analysis of interaction effects; however, these results are not included as positive findings here.…”
Section: Effect Of Rehydration or Hydration Status On Efmentioning
confidence: 99%